Comprehensive geriatric assessment is an independent prognostic factor in older patients with metastatic renal cell cancer treated with first-line Sunitinib or Pazopanib: a single center experience. Issue 2 (March 2021) - Pierantoni, Francesco; Basso, Umberto; Maruzzo, Marco; Lamberti, Evelina; Bimbatti, Davide; Tierno, Giuseppina; Bergo, Eleonora; Brunello, Antonella; Zagonel, Vittorina
Abstract: Background: There is poor data on the prognostic role of Comprehensive Geriatric Assessment (CGA) in older patients with metastatic renal cell carcinoma (mRCC) treated with first line Tyrosine Kinase Inhibitors (TKIs). Materials and Methods: We retrospectively reviewed the clinical charts of mRCC patients older than 70 years treated at our Institute with first-line Sunitinib or Pazopanib for at least 6 months. Every patient received a CGA at baseline and was identified as fit, vulnerable or frail according to Balducci's Criteria. We then assessed the impact of CGA category on survival, disease control and tolerability of TKIs. Results: We identified 86 eligible patients. Median age: 74.5 years, 56% males; 45.4% were fit, 37.2% vulnerable and 17.4% frail at CGA. There were no significant differences in the rate of Grade (G)1–2 and G3-4 toxicities, dose reduction rates, PFS and OS between Sunitinib and Pazopanib. Fit, vulnerable and frail patients achieved significantly different median PFS (18.9 vs 11.2 vs 5.1 months; p < 0.001) and OS (35.5 vs 14.6 vs 10.9 months; p < 0.001). Patients categorized as fit had higher chance of receiving a second-line treatment (66.6% vs 28.9% in vulnerable/frail; p = 0.002). The incidence of G3/4 events was significantly lower in the fit subgroup (19% vs 45% in vulnerable/frail; p = 0.0025). Conclusions: In our retrospective single-center experience, CGA could accurately discriminate patients with higher risk of experiencing G3/4 toxicities, shorter PFS, and lower chance of receiving a second line treatment. CGA strongly impacted on OS, independently from International mRCC Database Consortium (IMDC) classification.